Nanomaterial-facilitated protein direct electron transfers and their enhanced electrochemical biosensors - Guo, Chunxian (2011)
Nanomaterial-facilitated protein direct electron transfer (DET) has been extensively studied and widely applied in the development of electrochemical biosensors. However, the further enhancement of DET capacity necessary to develop high-performance biosensors for practical application remains a great challenge. To address this challenge, this PhD research project designs and fabricates novel nanocomposites with desirable properties to enhance protein DET capacity for the development of high-performance biosensors while exploring the fundamental insights in the effects of nanomaterial properties on protein DET behaviors and the mechanism behind enzymatic biosensing to gain fundamental knowledge. A nanocomposite of carbonized TiO2 nanotubes prepared by carbonizing TiO2 nanotubes to obtain a large reaction surface area and a high level of conductivity has been used to immobilize hemoglobin and explore its DET behaviors. Compared with TiO2 nanotubes, the nanocomposite is found to greatly enhance hemoglobin DET capacity, with the resulting biosensor exhibiting excellent bioelectrocatalytic activity toward H2O2 characterized by a rapid response time, a long linear detection range and a low detection limit. This study thus demonstrates that the conductivity of nanomaterials plays an important role in enhancing protein DET capacity and improving biosensing performance. A functional nanocomposite composed of mesoporous carbon with high conductivity and a large specific surface area, glucose oxidase (GOD) and an ionic liquid with good ionic conductivity that has been filled into a microcavity to fabricate a paste microelectrode exhibits enhanced GOD DET capacity and improved glucose biosensing performance.